The National SOM Survey 1989 - SOM Institute, University of Gothenburg (University of Gothenburg, 1990)
This dataset contains information from the fourth SOM-survey. The questionnaire was divided into seven subject fields: mass media; politics and society; energy, nuclear power and environment; Sweden's relation to other countries; residential environment, local conditions and leisure; radio listening; and background. Many of the questions are replications of questions asked in previous SOM-surveys, but there is also a number of questions not asked in previous surveys. The respondents had to give their opinion on how seriously a number of risks threaten life and health of the Swedish people. There are a number of questions concerning the European Community: the respondent´s opinion on mass media coverage of the EC-issue; the opinion on a Swedish membership´s influence on the environment, labour market, social security, economic development and the Swedish neutrality; and the attitude of the political parties toward a Swedish approach to the EC. The respondents had to indicate how satisfied they were with the local authority services in a number of areas. Other questions dealt with radio listening, how often and when the respondent listened to different radio channels. Furthermore the respondent had to compare regional and local radio.

Purpose:

The main purpose is to establish time series that enable researchers to analyse how various changes in society affect people's attitudes and behaviour.

Detta är den fjärde undersökningen i serien Riks-SOM, en nationell frågeundersökning med syfte att kartlägga den svenska allmänhetens vanor och attityder på temat samhälle, opinioner och medier.

1989 års undersökning består av sju sammanhållna delar: massmedier; politik och samhälle; energi, kärnkraft och miljö; Sveriges förhållande till omvärlden; boende, kommunala förhållanden och fritid; radiolyssnande samt bakgrundsuppgifter. Genom att frågor ställts på ett likartat sätt över tid finns det i SOM-serien tidsserier om bland annat medieanvändning, politik, kärnkraftsopinion och förtroende för olika samhällsinstitutioner och grupper.

Många frågor har ställts i en eller flera tidigare SOM-undersökningar, men i Riks-SOM 1989 finns även ett antal frågeställningar som ej använts i tidigare undersökningar. Bland annat fick respondenterna bedöma olika risker för svenska folkets liv och hälsa. Nya frågeställningar berörde även Sveriges förhållande till EG och vad ett eventuellt svenskt medlemskap skulle innebära för miljön, arbetsmarknaden, sociala tryggheten, den ekonomiska utvecklingen samt tilltron till svensk neutralitet. Respondenterna fick också ange hur nöjd man var med den kommunala servicen inom ett tiotal verksamhetsområden. Andra nya frågor berörde radiolyssnande, hur ofta och när man lyssnar på olika radiokanaler samt olika anledningar att lyssna på lokal- respektive närradio.

Syfte:

Huvudsyftet är att etablera tidsserier som gör det möjligt att analysera hur olika samhällsförändringar påverkar människors attityder och beteenden.
Den nationella SOM-undersökningen 1989
Riks-SOM 1989
Keywords: housing; boende; mass media; massmedia; defence; försvar; energy; energi; trust; förtroende; political interest; politiskt intresse; local government services; kommunal service; nuclear energy; kärnkraft; newspaper readership; tidnings läsekrets; membership; medlemskap; radio stations; radiostationer; television news; tv-nyheter; equipment; utrustning; professional ethics; yrkesetik; journalism; journalistik; advertising; reklam; press advertising; tidningsreklam; political influence; medborgarinflytande; economic conditions; ekonomiska villkor; internal politics; inrikespolitik; political parties; politiska partier; political leaders; politiska ledare; leisure time activities; fritidsaktiviteter; organizations; organisationer; public health risks; hälsorisker; radio listening; radiolyssnande; CORS; CORS; Media; Media; Environment and conservation; Miljö och naturvård; Energy and natural resources; Energi och naturresurser; Political behaviour and attitudes; Politiska beteenden och attityder; International politics and organisations; Internationell politik och organisationer; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap